Adsorption-assisted decontamination of Hg(ii) from aqueous solution by multi-functionalized corncob-derived biochar. Issue 67 (14th November 2018) - Faheem,; Bao, Jianguo; Zheng, Han; Tufail, Haseeb; Irshad, Sana; Du, Jiangkun
Abstract : Mercury (Hg) contamination of wastewater streams as a result of anthropogenic activities is a great threat to living organisms due to its acute toxicity. Abstract : Mercury (Hg) contamination of wastewater streams as a result of anthropogenic activities is a great threat to living organisms due to its acute toxicity. Therefore, current research is focused on the development of effective remediation technologies to protect human health and the environment. In this study, a novel chemical modification route was applied for the multi-functionalization of biochar in order to make it more efficient and selective for Hg(ii ) removal from aqueous solution. The amino-grafted modified biochar (AMBC) having multifunctional groups on its surface was successfully synthesized through the activation of excessively available carboxylic groups (–COOH) on pre-oxidized biochar (BC–COOH). The maximum Hg(ii ) adsorption capacity for the optimized amino-BC2 sample was 14.1 mg g −1, which was almost twice as that for pristine biochar (BC, 7.1 mg g −1 ). SEM, FTIR, and XPS techniques were applied for the confirmation of chemically grafted amino groups as well as the presence of residual –COOH groups on the biochar surface. Based on the batch adsorption data, adsorption kinetics and isotherms as well as XPS results, it was concluded that the Hg(ii ) removal mechanism was purely driven by chemisorption such as electrostatic interaction, surface complexation, ion exchange with no precipitation and crystalline material being adsorbed on the adsorbent surface. These research findings not only provide a suitable adsorbent for decontamination of Hg(ii ) from aqueous solution but also offer a new route for the multi-functionalization of biochar in order to make environment-friendly and inexpensive adsorbents.